2017
DOI: 10.1016/j.pscychresns.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructural deficits in 22q11.2 deletion syndrome

Abstract: Diffusion tensor imaging (DTI) studies in 22q11.2 Deletion Syndrome (22q11DS), a neurogenetic condition associated with psychosis, report brain white matter (WM) microstructure aberrations. Several studies report that WM disruptions in 22q11DS are similar to deficits in idiopathic schizophrenia. Yet, DTI results in 22q11DS are inconsistent. We used DTI to compare WM structure in 22q11DS individuals to healthy controls (HC) and explored WM differences in 22q11DS with (+) and without (−) psychosis spectrum sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 99 publications
0
14
0
Order By: Relevance
“…Few studies investigated white matter connectivity in patients with 22q11DS with and without UHR symptoms [( 14 , 17 , 18 ), Table 1 ]. Initial investigations used measures of white matter microstructural integrity, namely fractional anisotropy (FA), axial (AD), and radial diffusivity (RD) extracted from specific white matter pathways ( 14 , 18 ).…”
Section: Structural Connectivity In Patients With 22q11ds At High Rismentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies investigated white matter connectivity in patients with 22q11DS with and without UHR symptoms [( 14 , 17 , 18 ), Table 1 ]. Initial investigations used measures of white matter microstructural integrity, namely fractional anisotropy (FA), axial (AD), and radial diffusivity (RD) extracted from specific white matter pathways ( 14 , 18 ).…”
Section: Structural Connectivity In Patients With 22q11ds At High Rismentioning
confidence: 99%
“…Few studies investigated white matter connectivity in patients with 22q11DS with and without UHR symptoms [( 14 , 17 , 18 ), Table 1 ]. Initial investigations used measures of white matter microstructural integrity, namely fractional anisotropy (FA), axial (AD), and radial diffusivity (RD) extracted from specific white matter pathways ( 14 , 18 ). In a cohort of 22q11DS patients recruited from the University of Pennsylvania and the children hospital of Philadelphia Roalf and colleagues showed that individuals with 22q11DS with higher prodromal symptoms have a lower mean FA in the cingulate gyrus (CG), thus suggesting altered white matter integrity of this white matter bundle in association to a greater risk of psychosis.…”
Section: Structural Connectivity In Patients With 22q11ds At High Rismentioning
confidence: 99%
“…Disturbances in WM microstructural organization have been frequently reported in 22q11DS; however, studies to date have been relatively small, with highly variable findings. While many studies reported lower FA in 22q11DS compared to healthy controls (HC) in major WM tracts, including commissural, association and projection fibers [17][18][19][20][21][22], several others reported higher overall FA [23][24][25], or mixed findings across tracts [26][27][28][29][30][31]. Most studies reported consistent decreases in DTI-derived diffusivity measures (i.e., MD, RD, and AD), although some report mixed results [20] or higher WM diffusivity in 22q11DS [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…WM differences associated with psychosis are of interest in 22q11DS. Psychotic symptoms in 22q11DS have been associated with higher FA and lower WM diffusivities, but not always in the same regions across studies [22,25,30,31,33,34]. In addition, there is variability in deletion breakpoints; 85-90% of individuals with the deletion have a~3 Mb (A-D) deletion, containing 46 protein-coding genes, whereas~10% of cases have a nested 1.5 Mb (A-B) deletion [1].…”
Section: Introductionmentioning
confidence: 99%
“…More comprehensive reviews are found in 5–8 .Differences in fractional anisotropy and diffusivity parameters, e.g. lower fractional anisotropy in cingulum bundle and lower mean diffusivity in inferior longitudinal fasiculus 67 increase in fractional anisotropy in left inferior fronto-occipital fasiculus, and a decrease in RD in right IFOF; increase in right hemisphere FA and a decrease in right RD in right cingulum; increase FA decrease RD within the right thalamo-frontal tract; decrease radial diffusivity in right inferior longitudinal fasiculus 65 .22q11.2 duplication (chr22:19,037,332–21,466,726)Greater overall grey and whit matter volumes and cortical surface area. Reduced cortical thickness.…”
Section: Introductionmentioning
confidence: 99%